Enhancing cognition using transcranial electrical stimulation. (August 2015) - Santarnecchi, Emiliano; Brem, Anna-Katharine; Levenbaum, Erica; Thompson, Todd; Kadosh, Roi Cohen; Pascual-Leone, Alvaro
Highlights: tES allows to safely modulate brain activity by the means of transcranial electric fields. tES provides greater anatomical specificity respect to other cognitive enhancer like drugs. tES shows state and trait-dependency effects. Regulation about tES application outside laboratory environment are needed. Abstract : Noninvasive brain stimulation is being widely investigated to understand and modulate human brain function, and offers novel therapeutic approaches to neurologic and psychiatric disorders. Here, we focus on the growing interest in the potential of noninvasive brain stimulation, particularly transcranial Electrical Stimulation (tES), to enhance cognitive abilities in healthy individuals through the modulation of neuronal membrane potentials, specific brain oscillations or the delivery of electrical 'noise' to the system. We also emphasize the potential of tailoring tES parameters to individual trait and state characteristics for a personalized-medicine approach. Finally, we address the increasing use of tES by lay people, the ethical issues this raises, and consequently call for appropriate regulation.